1993
DOI: 10.1007/bf02247373
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind placebo-controlled study of tropisetron in the treatment of outpatients with generalized anxiety disorder

Abstract: The selective 5HT3 antagonist tropisetron was studied in 91 outpatients meeting DSM-III criteria for Generalized Anxiety Disorder. Following a placebo washout period of up to 1 week, one of three active treatments (tropisetron 0.5 mg, 5 mg, or 25 mg daily) or placebo was given for a further 3 weeks. After 7 days treatment termination rates due to inefficacy showed a statistically significant dose-related therapeutic effect of tropisetron. Similar effects were seen on the Hopkins Symptom Check List total score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Serotonergic signaling in prefrontal cortex demonstrates an important role in regulating sensation, emotion, and memory under normal and pathological conditions. Increased availability of 5-HT over 5-HT 2 and 5-HT 3 receptors increases anxiety, while blockade of 5-HT 3 receptors produces anxiolytic-like effect [10,11]. Several preclinical and clinical studies have suggested that 5-HT 3 receptors may be a relevant target in the treatment of affective disorders such as anxiety and depression [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Serotonergic signaling in prefrontal cortex demonstrates an important role in regulating sensation, emotion, and memory under normal and pathological conditions. Increased availability of 5-HT over 5-HT 2 and 5-HT 3 receptors increases anxiety, while blockade of 5-HT 3 receptors produces anxiolytic-like effect [10,11]. Several preclinical and clinical studies have suggested that 5-HT 3 receptors may be a relevant target in the treatment of affective disorders such as anxiety and depression [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the structure activity relationships (SAR) studies of aromatic substituents (Ar) on piperazine, p-chlorophenyl group (a series of 7) tends to exhibit better activities than those of other functional groups such as phenyl group (6), m-chlorophenyl group (8), and p-chlorophenyl(phenyl)methyl substituted ones (9). Among the p-chlorophenypiperazine substituted compounds, the compound 7b and 7h having one n-propyl group in pyrazole ring, were the most potent inhibitor that exhibited IC 50 values of 1.3 µM, which were comparable to the well-known 5-HT3A receptor antagonist MDL-72222 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…6 In CNS, 5-HT 3A receptors are known for nausea and vomiting, whereas are known for visceral pain such as irritable bowel syndrome in PNS. 7,8,9,10,11 In the early 1990s the introduction of 5-HT3 receptor antagonists into markets was perceived great success to attenuate side effects related with chemotherapy-induced emesis. It is well known that nausea and vomiting induced by chemotherapy of cancer patients result from activation of 5-HT3A receptors in the brain stem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, the compound was shown to be capable to reduce aversive properties of drug stimuli (Acquas et al 1990). In a re cent clinical trial, an anxiolytic effect of tropisetron was found in patients with generalized anxiety disorder (Lecrubier et al 1993). The present study explores the effects of the 5HT 3 antagonist tropisetron on sleep and sleep-associated secretion of cortisol and growth hor mone (GH) in humans.…”
mentioning
confidence: 99%